Fintech Syariah: Kolaborasi Teknologi dan Moral sebagai Instrumen Pembiayaan di Masa Depan - Imama Zuchroh (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
The progress and development of technology are so rapid. The financial industry is one of the areas that is receiving such a positive impact. Instrumen financing-based technology or financial technology is hotly discussed. Fintech seems to find momentum when the pandemic hits. When studying to work is required at home, business operations are reduced, and mobilization is limited. And the plague is also a disaster for the business world. So that capital becomes the effort of many business actors who experience the impact. So fintech, one of which is p2p lending, becomes an oasis with ease of access and wide range. Fintech Syariah also takes a role in these financial services. In this study, researchers want to give an idea of the power of sharia fintech in the financial industry. Based on data from OJK (Financial Services Authority), the number of Islamic fintech is still inferior to conventional fintech indeed currently growing, and the number of platforms is still limited. But the future of fintech sharia has reliable competitiveness and has a significant role in efficiency and service to the community in the financial industry. Thisajian uses a method of literature study on the phenomenon of the development of the financial technology era. The literature used in this paper comes from scientific journals both nationally and internationally and is supported by other scientific books. To analyze the future role of Islamic finance as the main payment instrument